The Vicious Circle of Quality in Ethiopian Higher Education - Woldegiyorgis, Ayenachew (International Higher Education, 2017)
While Ethiopian higher education is hailed for its expansion in the past years, its quality remains seriously challenged. The supply of low quality teachers and ill-prepared students, along with the high demand for new teachers forcing the government to massively recruit mediocre graduates, continues the vicious circle.